Scenarıo of Human Resources Management to Increase Commıtment of Mıllennıal Employees in Indonesıa Fınancıal Servıce Authorıty - Yanda Ekaputra Hermawan; Syamsul Maarif; Anggraini Sukmawati (APMBA (Asia Pacific Management and Business Application), 2022)
Currently, 70% of the composition of Indonesia Financial Service Authority (OJK) employees are millennials, therefore OJK has an interest in maintaining the commitment of these millennial employees to maintain OJK performance in the future. The purpose of this research is to develop HR management scenarios to increase the commitment of OJK millennial employees, which is preceded by a study on the effect of the generation gap, organizational culture, employee engagement, and location fit on organizational commitment using the Mann- Whitney test, PLS-SEM, and scenario planning. The results of the Mann-Whitney test show that currently there is a generation gap at OJK, further results from the PLS-SEM show that the generation gap, organizational culture, and employee engagement have a significant effect on organizational commitment, including the mediating effect of employee engagement and the moderating effect of location fit according to organizational commitment show the same result. Based on the test results, an HR management strategy was developed to increase the commitment of OJK millennial employees by using a scenario planning millennial approach in four scenarios: optimal, aggressive, selective, and minimal.